Scriptural Precision in the Malay World: Reforming the Jawi Vowel System for Qur’ānic Integrity Using the Nuqtah al-I’jām Method - Abdul Rahim, Mohd Hisyam; Faid, Muhamad Syazwan; Yusoff, Mohd Yakub Zulkifli Mohd (Journal of Islamic Thought and Civilization, 2026)
Jawi has long served as a principal script for transmitting Islamic knowledge and preserving Malay intellectual heritage. Yet in contemporary Malay, especially with the increasing presence of English loanwords, a persistent orthographic weakness has become more apparent: the absence of a dedicated representation for the é-taling vowel. In current usage, this vowel is typically rendered with the ya (ي) character, which is also used to represent the vowel /i/. When vowel diacritics are omitted, as is common in print and digital contexts, this overlap creates phonetic ambiguity and results in frequent misreadings (e.g., televisyen read as tilivisyen). Such ambiguity is particularly problematic in Qur’ānic literacy and religious instruction, where accurate pronunciation is vital for conveying meaning. This study analysed 70 Malay words containing the é-taling sound, selected through a structured review of entries in Kamus Dewan (4th ed.). Through qualitative inductive analysis combined with comparative orthographic examination, the study revealed systematic patterns of confusion between the é-taling and /i/ vowel sounds in Jawi spelling. Drawing on the historical precedent of Jawi character expansion using the Nuqtah al-Iʿjām method, the study proposes a new character derived from the ya base to represent the é-taling vowel distinctly. This reform offers a practical solution to improve spelling precision, reduce mispronunciation, and support the continued relevance of Jawi in modern Malay usage and Qur’ānic education.